Business Model Inovation of Batik Kembang Turi Sidoarjo: A Lesson from the Pandemics - Azhar, Ratih Mukti; Evanthi, Ayundha; Syarifudin, Adinda Rahmawati; Ratri, Lintang Mutiara (Future Science, 2023)
The recovery of the national economy after the COVID-19 pandemic is inseparable from the important role of MSMEs as a pillar of economic support. Its existence contributes to the gross domestic product by 61.97%. This phenomenon significantly affects the MSME business and triggers each business actor in this field to continue to develop their business, including Batik Kembang Turi Sidoarjo, which is one of the business actors that raises the potential of Batik as one of the local wisdom in Sidoarjo. This study was conducted to determine the description of business model innovation in Batik Kembang Turi Sidoarjo in facing the pandemic crisis. This research uses a qualitative approach to analyze information and obtain factual findings to understand these conditions through information on Business Model Innovation in MSMEs. The results show that BMI changes in Batik Kembang Turi Sidoarjo which refer to the Concept of BMI Conceptual Model Magnitude are in Quadrant Type 4 where high novelty and high complexity of changes in the elements of the business model. Changes in services where Batik Kembang Turi began to change their services to the tourism sector arose due to changes in consumer segments and value propositions radically changing the infrastructure system due to the extreme impact of the pandemic on their business and environment.